(untitled) (Konferensiyalar | Conferences, 2024)
This article deals with the effectiveness of the process approach in enhancing English as a Foreign Language (EFL) writing abilities. The process approach to writing emphasizes multiple stages of writing, including pre-writing, drafting, revising, and editing, which encourages learners to focus on the writing process rather than solely on the final product. The annotation cites relevant research studies to highlight the positive impacts of the process approach on EFL writing proficiency. The paper describes that the approach encourages students to develop a deeper understanding of the writing process, resulting in improved writing quality, increased engagement, and more positive attitudes towards writing. It emphasizes the importance of prewriting, drafting, revising, and editing stages, along with feedback and peer assessment, to enhance EFL writing abilities. The writer posits that adopting an instructional method centered around that students could lead to an improvement in their writing proficiency. Additionally, the author proposes various techniques and strategies that have the potential to enhance the writing abilities of students within the context of English as a Foreign Language (EFL) education.